(untitled) (Scottish Historical and Archaeological Internet Reports, 2009)
All of the sherds were small or abraded and had no diagnostic attributes. Fabric has yet to be proved a reliable indicator of date. Most of the pottery comes from high spits and topsoil contexts. As such it does not relate to the Mesolithic use of the site.